Основные результаты комплексных исследований ЮгНИРО в Азово-Черноморском бассейне и Мировом океане - Gubanov, E.P.; Southern Scientific Research Institute of Marine Fisheries and Oceanography (YugNIRO) (YugNIRO, 2004)
Problems of state of commercial fish species and invertebrate stocks in the Azov and Black Seas Basin and in some areas of the World Ocean are considered; oceanographic characteristics are presented taking into account natural and anthropogenic factors. Assessment of the by-catch value in purse seine fisheries in the North Equatorial Area of the Indian Ocean is given. Data on information support of the YugNIRO fisheries research are given; prospects of computer processing of echometric surveys of fish schools are shown. New data on 4 diphyllobothriidae species paraziting in Pinnipedia in the Antarctic are presented. Рассмотрены вопросы состояния запасов промысловых видов рыб и беспозвоночных в Азово-Черноморском бассейне и некоторых районах Мирового океана, приведены океанографические характеристики с учетом природных и антропогенных влияний, дана оценка величины прилова кошелькового флота в Северном экваториальном районе Индийского океана. Приведены данные информационного обеспечения рыбохозяйственных исследований ЮгНИРО, показаны перспективы компьютерной обработки материалов эхометрических съемок рыбных скоплений. Представлены новые сведения о 4 видах дифиллоботриид, паразитирующих у ластоногих в Антарктике. Published